2012
DOI: 10.3390/buildings2010033
|View full text |Cite
|
Sign up to set email alerts
|

The Potential for the Use of the Occupants’ Comments in the Analysis and Prediction of Building Performance

Abstract: Abstract:The authors investigated the occupants' perceptions of 47 commercial and institutional buildings worldwide. These investigations involved the personal distribution and collection of a questionnaire survey seeking the occupants' perceptions (scored on a 7-point scale) of some 45 factors: Operational; Environmental (including temperature, air quality, lighting, and noise); Personal Control; and Satisfaction (including design, needs, comfort overall, productivity, and health). Occupants were also invited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 10 publications
3
20
0
Order By: Relevance
“…The present study fills the research gap by examining the relationship between occupants' satisfaction and indoor environment quality, and the effect the problems experienced with noise level may have on general satisfaction and the perceived acoustic quality in LEED-certified and conventional residential buildings. Similarly to [10,30,31], for example, this study falls into the category of post-occupancy evaluation by using the subjective opinion of users in the evaluation of indoor environment and building performance.…”
Section: Green Buildings and Acoustic Quality Studiesmentioning
confidence: 99%
“…The present study fills the research gap by examining the relationship between occupants' satisfaction and indoor environment quality, and the effect the problems experienced with noise level may have on general satisfaction and the perceived acoustic quality in LEED-certified and conventional residential buildings. Similarly to [10,30,31], for example, this study falls into the category of post-occupancy evaluation by using the subjective opinion of users in the evaluation of indoor environment and building performance.…”
Section: Green Buildings and Acoustic Quality Studiesmentioning
confidence: 99%
“…Zalejska-Jonsson (2012) also advocates using interviews with property managers to gather contextual information about a building. Baird and Dykes (2012) reported a ratio of negative comments to positive comments and suggested that when "the ratio exceeds a value of 10:1… clearly there are issues requiring attention." Similar ratios will be reported throughout the chapter, as well as analysis of the usefulness of this method.…”
Section: Methodsmentioning
confidence: 99%
“…Almost all respondents offered at least one comment, with only 5.5% (n=9) offering no comments. For context, in commercial and institutional buildings 34% of people commented in Baird and Dykes (2012), suggesting that residential respondents are far more likely to comment. Of the 700 comments received, 255 offered praise while 445 offered criticism, for an overall ratio of 1.8:1.…”
Section: Response Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…They have lower construction costs, allowing for significant space savings and, according to designers, facilitate communication between workers, thus, improving collaboration, as well as the exchange of ideas. Unfortunately, many studies show that few workers love to work in them since the buzz of chatter is distracting and there is the lack of privacy that is necessary to work quietly [1][2][3].…”
Section: Introductionmentioning
confidence: 99%